Human fibronectin: molecular cloning evidence for two mRNA species differing by an internal segment coding for a structural domain. - Kornblihtt, A R (1984)
Two different fibronectin (FN) mRNA species were detected in the human cell line Hs578T. One species, mRNA I, contains an additional 270 nucleotide long insert (ED) that encodes exactly one of the internally repeated structural domains of the protein. The 90 amino acid extra domain belongs to the so-called type III homology and it is located in the carboxy-terminal half of FN, in between the cell attachment and the heparin binding sites of the protein. The evidence of two mRNAs is provided by the isolation and characterisation of four independent cDNA clones from a library prepared with a synthetic oligonucleotide primer, and it was confirmed by S1 nuclease analysis of cDNA/mRNA hybrids. This kind of analysis also showed that in the human cell line, mRNA I is present at a lower level than mRNA II (the mRNA species without the ED), whilst in human liver, mRNA I is virtually undetectable. Since liver tissue has recently been reported to be the source of plasma FN, our results indicate that the presence of the ED insert could be a particular feature of cellular FN.